2000
DOI: 10.2337/diabetes.49.12.1992
|View full text |Cite
|
Sign up to set email alerts
|

Early graft failure of xenogeneic islets in NOD mice is accompanied by high levels of interleukin-1 and low levels of transforming growth factor-beta mRNA in the grafts.

Abstract: Early graft failure, graft rejection, and autoimmune recurrence remain unresolved issues in islet xenotransplantation in type 1 diabetes. The first aim of this study was to examine the existence of early graft failure in spontaneously diabetic autoimmune NOD mice after rat islet transplantation under technically controlled circumstances. The second aim was to examine the mediators of this early xenograft dysfunction. First, we demonstrated a higher percentage of early xenograft failure (48%) in spontaneously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 25 publications
2
51
0
4
Order By: Relevance
“…We have previously shown [64] and confirmed in this study that a state of inflammation with high local expression of IL-1 is demonstrated immediately after (8-h) islet transplantation in autoimmune NOD mice. IL-1 expression was also increased in BALB/c mice isografts, suggesting that this is probably secondary to non-specific tissue damage associated to the early engraftment.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously shown [64] and confirmed in this study that a state of inflammation with high local expression of IL-1 is demonstrated immediately after (8-h) islet transplantation in autoimmune NOD mice. IL-1 expression was also increased in BALB/c mice isografts, suggesting that this is probably secondary to non-specific tissue damage associated to the early engraftment.…”
Section: Discussionsupporting
confidence: 87%
“…To date, the pathophysiology of islet primary non-function is incompletely understood, but we have previously shown that it is of great importance in autoimmune hosts (spontaneously diabetic NOD mice) and seems to be associated with nonspecific inflammation at the implantation site, with a major role being played by IL-1β and free radicals (nitric oxide) [23,34]. This role of IL-1β in primary non-function also explains the difference in primary non-function between Irf-1 −/− and Stat-1 −/− islets transplanted into NOD mice, as IRF-1 is not only controlled by IFN-γ, but is also partially regulated by IL-1β, in contrast to STAT-1.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6 mice were used as controls and were obtained from stocks purchased from Harlan (Horst, the Netherlands). NOD mice, inbred in our animal facility (Proefdierencentrum Leuven, Leuven, Belgium) since 1989, were used as diabetes-prone animals, with diabetes detected and defined as described [23]. All mice were housed under semi-barrier conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations